DNA Copy Number Changes at 8q11–24 in Metastasized Colorectal Cancer - T. E. Buffart; J. Coffa; M. A. J. A. Hermsen; B. Carvalho; J. R. M. van der Sijp; B. Ylstra; G. Pals; J. P. Schouten; G. A. Meijer (Cellular Oncology, 2005)
Background: C-Myc, a well-known oncogene located on 8q24.12–q24.23, is often amplified and over-expressed in both primary and metastasizing colorectal cancer. In addition, PRL-3 (also known as PTP4A3), a tyrosine phosphatase located on 8q24.3, is amplified in colorectal cancer metastasis. Beside PRL-3 and c-myc, other oncogenes located on the 8q23–24 region might be involved in this process. Therefore, the present study aims to correlate DNA copy number status of a series of genes at 8q23–24 in colorectal cancer at high resolution in correlation to metastatic disease. Materials and Methods: Thirty-two cases of colorectal cancer, 10 stage B1, 10 B2 and 12 D (Astler–Coller) with their corresponding liver metastasis and one colorectal cell line (colo205, previously analyzed by array-CGH), were included in this study. A chromosome 8 specific MLPA probe mixture was used to analyze the presence of DNA copy number changes. The probe mixture contained 29 probes covering 25 genes on chromosome 8, as well as 6 control probes on other chromosomes. Results and Discussion: MLPA results obtained of the colo205 colorectal cell line were comparable with previous array-CGH results, thus validating the MLPA probe mixture. Astler–Coller B1 and B2 colorectal cancers differed significantly in DNA copy number of the genes, MOS (p = 0.04), MYC (p = 0.007), DDEF1 (p = 0.004), PTK2 (p = 0.02) and PTP4A3 (p = 0.04). When comparing these with Astler–Coller D primary tumors, significant differences were seen for several genes as well (MYC (p < 0.000), DDEF1 (p < 0.000), SLA (p < 0.000), PTK2 (p < 0.000), PTP4A3 (p = 0.002), and RECQL4 (p = 0.01)). When comparing primary Astler–Coller D tumors and their corresponding liver metastases, a similar pattern of gains and losses was observed. Most of the liver metastases showed higher DNA copy number ratios than the corresponding primary tumors, but this difference was only significant for TPD52 (p = 0.02) and EIF3S6 (p = 0.007). Conclusion: In addition to c-myc, multiple genes on chromosome 8 differed significantly between primary colorectal cancers with and without liver metastases. This observation is consistent with the concept that clinical behaviour, like risk of liver metastasis, is determined by the genomic profile that is already present in the primary tumor.